Degradation of Glycine and Alanine on Irradiated Quartz - Pawlikowski, Maciej (Springer Netherlands, 2013)
Recent researches suggest participation of minerals in the formation of life under primordial conditions. Among all of the minerals, quartz seems to be one of the most probable to take part in such processes. However, an external source of energy is needed, e.g. electric discharge. A device simulating the proposed conditions was designed and was used to simulate prebiotic conditions. Investigation of processes occurring during the stimulation of quartz with electric discharge was studied by means of Ultraviolet–visible (UV–VIS) spectroscopy, in order to monitor the generation kinetics of free radicals. Additionally, infrared spectroscopy was applied to identify chemical reaction products created in a solution of alanine or glycine, in the presence of quartz treated with electric discharge. Formation of increased amounts of free radicals, compared to experiments performed without quartz and/or amino acid, is reported, along with identification of possible degradation products of alanine. No synthetic reactions were observed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11084-013-9328-3) contains supplementary material, which is available to authorized users.